2015
DOI: 10.18632/oncotarget.3551
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BET bromodomains as a therapeutic strategy for cancer drug discovery

Abstract: As a conserved protein interaction module that recognizes and binds to acetylated lysine, bromodomain (BRD) contains a deep, largely hydrophobic acetyl lysine binding site. Proteins that share the feature of containing two BRDs and an extra-terminal domain belong to BET family, including BRD2, BRD3, BRD4 and BRDT. BET family proteins perform transcription regulatory function under normal conditions, while in cancer, they regulate transcription of several oncogenes, such as c-Myc and Bcl-2. Thus, targeting BET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
161
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(165 citation statements)
references
References 95 publications
0
161
0
Order By: Relevance
“…Collectively, these data suggest that loss of Polycomb repressive function in IBCs might be due to epigenetic alteration of PRC1 and PRC2 by several microRNA targeting CBX7 and EZH2, resulting in altered H3K27trimethylation and H3K27 acetylation. Development of therapies targeting epigenetic processes in cancer has gained increasing focus with study of HDAC and DNA methyltransferase inhibitors and more recently of BET bromodomain inhibitors (48). Indeed, recent studies of malignant peripheral nerve sheath tumors (MPNST) have showed that alterations of PRC2 subunits lead to the amplification of Ras-driven transcription and confer sensitivity to BET bromodomain inhibitors (49,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, these data suggest that loss of Polycomb repressive function in IBCs might be due to epigenetic alteration of PRC1 and PRC2 by several microRNA targeting CBX7 and EZH2, resulting in altered H3K27trimethylation and H3K27 acetylation. Development of therapies targeting epigenetic processes in cancer has gained increasing focus with study of HDAC and DNA methyltransferase inhibitors and more recently of BET bromodomain inhibitors (48). Indeed, recent studies of malignant peripheral nerve sheath tumors (MPNST) have showed that alterations of PRC2 subunits lead to the amplification of Ras-driven transcription and confer sensitivity to BET bromodomain inhibitors (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are defined by a length ranged from 200 bp to 100 kbp and their number is in constant increase: 48,680 lncRNAs are at present identified (5)(6)(7). LncRNAs are important regulators coordinating expression of protein-coding genes nearby (cis-regulation) or at distance (trans-regulation).…”
Section: Introductionmentioning
confidence: 99%
“…The BET subfamily of bromodomain-containing proteins is involved in a number of hematological and solid tumors (15,17). Currently, several active clinical trials aiming to treat malignancies are using BET inhibitors, such as FT-1101, ZEN003694, BMS-986158, INCB054329, RVX-208, I-BET 762, OTX 015, CPI-0610, and TEN-010 (www.clinicaltrials.gov).…”
Section: Discussionmentioning
confidence: 99%
“…Besides bone formation, bone homeostasis is maintained by the balance between osteoblastic bone formation and osteoclastic bone resorption, whereas the growth of long bones is from endochondral ossification of chondrocytes derived from cartilage (15). Previous studies have shown that BET inhibitors may affect osteoclastogenesis (14) and the bone-associated tumor vicious cycle (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation